EFEKTIVITAS PENERAPAN PENDEKATAN DEEP LEARNING DALAM MATA PELAJARAN INFORMATIKA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD KRISTEN TUNAS GLORIA KUPANG - Elisabet Remenda; Diana Yanni Ariswati Fallo; Maria magdalena Beatrice (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze how the integration of dialogic learning and immersive learning within a Project Based Learning (PjBL) framework, using illustrated Jataka stories from the Borobudur Temple reliefs, can improve creativity, literacy skills, and understanding of moral values ​​​​of elementary school students. The background of this study lies in the low level of higher-order thinking skills (HOTS) among Indonesian students and the need for a contextual and adaptive learning approach to the challenges of the 21st century. Jataka reliefs were chosen as a learning resource rich in moral values ​​​​and narrative visuals, so that they are relevant to the characteristics of students at the concrete operational stage. This study used a qualitative approach with a case study design involving Phase B students at Kanisius Wanurejo Borobudur Elementary School. Data collection techniques included participant observation, semi-structured interviews, and student reflection journals. Data analysis followed the Miles & Huberman model, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that the integration of dialogic learning, immersive learning, and PjBL provides students with opportunities to think critically, express ideas, collaborate, and develop deeper moral understanding. The use of illustrated stories has been shown to be effective in enhancing imagination, improving literacy skills, and connecting concepts to real-life experiences. These findings confirm that local culture-based learning through the Jataka narrative project is an innovative and effective approach to fostering creativity, literacy, and character development in elementary school students.